Introduction of a Methodology for Deep Energy Retrofitting of Post-War Residential Buildings in Central Europe to Zero Energy Level - Antonin Lupisek; Martin Volf; Petr Hejtmanek; Katerina Sojkova; Jan Tywoniak; Peter Op’t Veld (Communications - Scientific letters of the University of Zilina, 2016)
Buildings are responsible for 35% of greenhouse gas emissions released in Europe. The highest potential for reduction of the environmental impacts is in the existing buildings’ energy efficiency improvement. The paper introduces a development of new methodology for a rapid deep energy retrofitting of existing buildings applicable to residential housing stock in Central Europe. It briefly describes the steps from production of building information model of existing building to complete renovation. It presents experience from pre-production phases on a case study from the Czech Republic. Technical and non-technical barriers to be solved in the near future are summarised in the discussion.